2011
DOI: 10.1021/jp202152m
|View full text |Cite
|
Sign up to set email alerts
|

Long-Distance FRET Analysis: A Monte Carlo Simulation Study

Abstract: A new method for extending the utilizable range of Förster resonance energy transfer (FRET) is proposed and tested by the Monte Carlo technique. The obtained results indicate that the efficiency of FRET can be significantly enhanced at a given distance if the energy transfer takes place toward multiple acceptors that are closely located on a macromolecule instead of a single acceptor molecule as it is currently used in FRET analysis. On the other hand, reasonable FRET efficiency can be obtained at significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…Blue and red columns). The (ratio) A values obtained in the reassembled ferritins were negatively related to the increase of acceptor subunits, in accordance with previously reported studies on multiple-acceptor systems where insufficient emitting donors yield an insufficient excitation of the acceptors via energy transfer (37,38). The absence of this tendency in the corresponding disassembled mixtures confirmed the reassembly of the ferritins at the pre-incubated donor:acceptor ratio.…”
Section: Fret To Characterize the Formation Of Isoferritin Hybridssupporting
confidence: 90%
“…Blue and red columns). The (ratio) A values obtained in the reassembled ferritins were negatively related to the increase of acceptor subunits, in accordance with previously reported studies on multiple-acceptor systems where insufficient emitting donors yield an insufficient excitation of the acceptors via energy transfer (37,38). The absence of this tendency in the corresponding disassembled mixtures confirmed the reassembly of the ferritins at the pre-incubated donor:acceptor ratio.…”
Section: Fret To Characterize the Formation Of Isoferritin Hybridssupporting
confidence: 90%
“…From this we observed that the highest FRET efficiency was achieved at A/D = 2.12) which was used for the subsequent development of our FRET screening assay. This result can be understood from the theoretical investigation by Bojarski et al [52], which suggested that the FRET efficiency can be significantly increased at a given distance if the energy transfer takes place towards multiple acceptors instead of a single acceptor molecule. Moreover, too little or too much of either fluorophore can also significantly reduce the FRET signals due to self-quenching and/or insufficient energy transfer [56].…”
Section: Resultsmentioning
confidence: 86%
“…On the other hand, low F/P ratios will lead to very low signals which may not be easy to differentiate from the background noise. Recent theoretical and experimental studies have also indicated that FRET efficiency can be significantly increased by optimizing the F/P ratio, especially when the energy transfer takes place to multiple acceptors [52], [53]. Following these facts, we optimized the conjugation protocol to obtain F/P ratios for our fluorophore-protein conjugates to have strong FRET activity, and also for the subsequent determination of the dissociation constant (K d ) of the LFA-1/D1-D2-Fc interaction as well as in screening assay development to classify inhibitors of the interaction.…”
Section: Resultsmentioning
confidence: 99%
“…In order to increase the distance between the donors and acceptors for FRET, researchers added a third chromophore as a bridge of energy transfer to extend distance between the donors and receptors for amplifying energy transfer [36]. For instance, Elke Haustein et al [37] designed two coupled FRET pairs by utilizing three different dyes including Rhodamine Green, TAMRA, and Cy5 labeled on the different sites of the DNA, TAMRA as donor/bridging dye, which transferred the energy to the Cy5.…”
Section: Introductionmentioning
confidence: 99%